Is Weight Loss the Main Driver for A1C Improvement by Glucagon‐Like Peptide 1 (GLP‐1) Receptor Agonists? A 2.5‐Year Analysis in Real‐World Clinical Practice - Marwa Al‐Badri; Shilton Dhaver; Osama Hamdy (Journal of Diabetes)
ABSTRACT Background Glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) are established treatment options for type 2 diabetes (T2D). In addition to their glycemic benefit, GLP‐1 RAs also induce weight loss by suppressing appetite via hypothalamic pathways. However, it remains unclear whether weight reduction is the primary driver of glycemic improvement. Methods We retrospectively evaluated 256 patients with T2D who were treated with exenatide (n = 84), dulaglutide (n = 99), or semaglutide (n = 73) for 2.5 years without interruption in real‐world clinical practice. Body weight and A1C were measured every 6 months. Baseline characteristics included an average age of 61.8 ± 11.9 years, 51.5% female, diabetes duration of 12.9 ± 8.3 years, weight of 103.1 ± 20.7 kg, BMI of 35.7 ± 7.5 kg/m2, and A1C of 8.2% ± 1.5%. Patients were stratified into tertiles based on percentage weight change at 2.5 years within the overall cohort and for each GLP‐1 RA group. Results The first tertile experienced an average weight loss of −12.2% ± 5.7% (p < 0.0001), the second tertile lost −3.5% ± 1.4% (p < 0.0001), and the third tertile gained +2.8% ± 3.4% (p < 0.0001). The average changes in A1C were − 0.98 ± 1.8% (p < 0.0001), −0.56% ± 1.4% (p < 0.001), and −0.19% ± 1.9% (p = 0.4), respectively. A1C strongly correlated with weight change (p < 0.001). The same observations were reproducible in each medication group. Conclusions These findings suggest that the long‐term improvement in glycemic control associated with GLP‐1 RA therapy is primarily driven by weight loss rather than any other intrinsic effect of GLP‐1 RA. This highlights the importance of weight reduction as a key therapeutic target for optimizing glycemic outcomes in patients with T2D receiving GLP‐1 RAs.